Pelatihan Maulid Habsyi di Madrasah Aliyah Negeri (MAN) Tembilahan Kabupaten Indragiri Hilir - Hasnawati Hasnawati; Masriani Masriani (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Teachers as facilitators and motivators in schools have a role in realizing the development of the talents of their students, especially the reading skills of habsyi. In this case, students should be given supervision, coaching, and motivation so that their talents can develop optimally. Some did not master their religious arts, and some of them also did not participate in these activities because they feel did not have talent in that field, especially in terms of the reading skills of habsyi. The reading skills of Habsyi can be developed through training or learning that is carried out outside of teaching hours, namely extracurricular activities that are developed through more directed and systematic coaching. Therefore, to develop the students' potential in the Maulid habsyi, it is necessary to provide continuous supervision, attention, and motivation from all teachers and school principals. This is because extracurricular coaching that is less than optimal will result in less-than-optimal reading skills of students.